Issues of identity and emotions in the hybridization of NHS hospitals: The role of activity-based costing as a strategy - Major, M.; Clegg, S.; Conceição, A. (Financial Accountability and Management, 2025)
Public hospitals are becoming increasingly hybrid in their institutional logics in response to changing strategies. We conducted a longitudinal, in-depth case study involving five public hospitals, the Portuguese Ministry of Health, and its agencies to examine the role of activity-based costing (ABC) in the hybridization of the sector. Theoretically, we drew on Thornton et al.’s metatheoretical framework, as well as literature on identity and emotions, to inform the study. In doing so, we recognize that constructing a new hybrid institutional logic within a field is a complex endeavor that spans multiple levels of analysis and that actors at the intraorganizational level play a central role in shaping institutional processes. Our findings highlight the role of clinicians’ emotions and identity change in the construction of a new hybrid logic at the microlevel. We found that conflicts of identity and negative emotions triggered by the implementation of ABC—such as distrust, fear, and anxiety—hindered the development of hybridization at higher institutional levels. We conclude that only through positive emotional processes can a new hybrid logic gradually develop at the microlevel and accrete at the field level.